Introduction to the special section: Navigating the boundaries in global training and education: new literacies, competencies, and practices - Brewer, Pam Estes (2013)
The two tutorials and one research article in this special section focus on navigating the boundaries in global training and education. Two additional papers on this topic will appear in the next issue (September 2012).